The cultural landscape of the Hyblaean Mountains between the 3rd century BC and the 2nd century AD in the light of multidisciplinary research - Chowaniec, Roksana (Gerión. Revista de Historia Antigua, 2024)
Power in Syracuse was taken by Hiero II in 270 BC. Then the Hyblaean Mountains, much of which belonged to Syracuse, underwent changes and entered a period of transformations. When the First Punic War began Hiero II signed a treaty with Rome, which ensured long-term stabilization, economic growth and thorough development of the kingdom. His reign was the last period in which Syracusan territory flourished and enjoyed independence. After his death in 215 BC and the fall of Syracuse, the Romans confiscated Syracusan lands and annexed the towns allied with metropolis, also in the Hyblaean Mountains. It should be emphasized that this region represented a deeply-rooted Hellenistic heritage –evident in a variety of public and private buildings associated with developed culture, art, the self-confidence of the inhabitants. But new architecture, everyday objects, inscriptions and other components present already new influences. It is associated with the Roman migration to the newly conquered lands. Later, this region played a role during the conflict between Sextus Pompey and Octavian with its long-term consequences. Thanks to the archaeological sources can be assumed that the result was an influx of Roman veterans as settlers and new material culture, agriculture, breeding and know-how here